2017
DOI: 10.1155/2017/9485826
|View full text |Cite
|
Sign up to set email alerts
|

Pullout Characteristics of Geosynthetics Reinforced Earth Using Multilayer Spreading Pullout Test

Abstract: Pullout test equipment for examining pullout characteristics in a reinforced earth structure is relatively larger than direct shear testing machines and requires much time and expenses in preparing samples. Moreover, because of irregular stress distributions with respect to the length of reinforcements, it is difficult to analyze pullout test results. In this study, we developed a multilayer spreading pullout apparatus enabling the pullout test in the order of a top stage, middle stage, and bottom stage with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…From the test results, it can be observed that pullout resistance forces have increased with an increase in normal stresses from 37 to 110 kPa, and all the maximum pullout forces were achieved within the deformation range of 50 to 80 mm. Beyond this, the pullout resistance forces were observed to be decreased because of particles rearrangement among themselves and followed by reinforcement pullout [17]. The improvement in pullout resistance against normal load is due to the development of passive resistance of transverse reinforcement.…”
Section: Pullout Frictional Characteristics Between Pond Ash and Gmentioning
confidence: 98%
“…From the test results, it can be observed that pullout resistance forces have increased with an increase in normal stresses from 37 to 110 kPa, and all the maximum pullout forces were achieved within the deformation range of 50 to 80 mm. Beyond this, the pullout resistance forces were observed to be decreased because of particles rearrangement among themselves and followed by reinforcement pullout [17]. The improvement in pullout resistance against normal load is due to the development of passive resistance of transverse reinforcement.…”
Section: Pullout Frictional Characteristics Between Pond Ash and Gmentioning
confidence: 98%
“…Therefore, taking targeted control measures combined with geological conditions is the basis and premise of achieving favorable governance effects. At present, the traditional slope stability control technology, such as unloading, antislide pile, anchor-plate retaining, and reinforced soil [14][15][16][17][18], can hardly achieve the desired control effect in slope engineering with the abovementioned geological conditions given the limitations in their technical features.…”
Section: Introductionmentioning
confidence: 99%